The Company Size as a Moderator of the Effect of Corporate Social Responsibility (CSR) and Sales Growth on the Financial Performance of Industrial Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2021-2024 - Nabilah, Dwi Uthari; Hayati, Hikmatul; Pangaribuan, Laspita; Rosini, Iin (The Future of Education Journal, 2026)
This study aims to analyze the simultaneous effects of corporate social responsibility and sales growth on company financial performance, to analyze whether corporate social responsibility has a positive effect on company financial performance, to analyze whether sales growth has a positive effect on company financial performance, and to analyze whether company size moderates the effect of corporate social responsibility on company financial performance. To analyze whether corporate social responsibility has a positive effect on company financial performance. The population in this study was industrial sector companies listed on the IDX for the period 2021-2024, totaling 65 companies. The sampling technique used was purposive sampling, resulting in a research sample of 18 companies. The data was processed using E-views 12 software, and the research method used was quantitative with a descriptive approach. The analysis used was multiple linear regression analysis and moderated regression analysis. The results of this study indicate that corporate social responsibility and sales growth simultaneously affect company financial performance. Corporate Social Responsibility does not have a positive effect on company financial performance. Sales growth does not have a positive effect on company financial performance. Company size cannot moderate the effect of corporate social responsibility on company financial performance. Company size cannot moderate the effect of sales growth on company financial performance.